Relationship between Knowledge and Family Support Regarding Postpartum Implant Contraception in Postpartum Mothers - Riswanti; April Artinanda; Syarifah Masita; Nur Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Implant contraception is an effort to prevent pregnancy. Efforts made in contraceptive services can be temporary or permanent, where contraception is an important component in reproductive health services so that it can reduce the risk of death and morbidity in pregnancy. Objective: To determine the relationship between knowledge and postpartum implant contraception in postpartum mothers at the Tamalate Health Center in 2025. Method: This research design uses an analytical study with a cross-sectional approach. The population in this study were all mothers giving birth at the Tamalate Health Center in Makassar City, totaling 50 people. The sample in this study were mothers giving birth with a sampling technique using total sampling, which means that the entire population was used as a research sample so that the sample obtained was 50 people. Data collection was carried out using a research instrument in the form of a questionnaire. Data analysis includes univariate analysis by finding the frequency distribution, bivariate analysis using the chi square test. Results: There is a relationship between knowledge and postpartum implant contraception at the Tamalate Health Center in Makassar City in 2025, p value = 0.000 <0.05. There is a relationship between family support and postpartum implant contraception in the Tamalate Health Center Work Area, Makassar City in 2025, p value = 0.001 <0.05. Conclusion: there is a relationship between knowledge and postpartum implant contraception in postpartum mothers in the Tamalate Health Center Work Area, Makassar City in 2025.